Experimental validation of a multiphysics model for the microwave-assisted pasteurization of apple juice - Tamires K. Oishi; Eduardo V.S. Pouzada; Jorge A.W. Gut (Digital Chemical Engineering, 2022)
A microwave cavity designed for continuous flow thermal processing of liquid foods was evaluated for the pasteurization of fresh apple juice. A three-dimensional model was built based on the assembly of the MicroThermics Lab25-UHT/HTST EHVH unit (2450 MHz, 6 kW). Simulations were implemented using the Finite Element Method in COMSOL Multiphysics 6.0. The physics for electromagnetic waves, laminar flow and heat transfer were combined iteratively to solve and predict the electric field intensity, the velocity profile and the temperature distribution within the fluid domain. To validate the model, cloudy apple juice was processed in the unit with flow rates of 0.4 and 0.8 L/min and pasteurization temperatures of 70, 80 and 90 °C. Cavity outlet temperature was measured and compared with simulation results. Multiphysics model showed good temperature prediction with average absolute error of 1.6 °C. Temperature distribution results were useful for determining hot and cold spots within the tube and showed an important temperature gradient at the outlet cross section of the tube. The main results show that the proposed model is reliable for predicting time-temperature histories during thermal processing, and can be used for process evaluation and product quality improvement.